Radiation dose evaluation in 64-slice CT examinations with adult and paediatric anthropomorphic phantoms - Fujii, K (The British Institute of Radiology., 2009)
The objective of this study was to evaluate the organ dose and effective dose to patients undergoing routine adult and paediatric CT examinations with 64-slice CT scanners and to compare the doses with those from 4-, 8- and 16-multislice CT scanners. Patient doses were measured with small (<7 mm wide) silicon photodiode dosemeters (34 in total), which were implanted at various tissue and organ positions within adult and 6-year-old child anthropomorphic phantoms. Output signals from photodiode dosemeters were read on a personal computer, from which organ and effective doses were computed. For the adult phantom, organ doses (for organs within the scan range) and effective doses were 8–35 mGy and 7–18 mSv, respectively, for chest CT, and 12–33 mGy and 10–21 mSv, respectively, for abdominopelvic CT. For the paediatric phantom, organ and effective doses were 4–17 mGy and 3–7 mSv, respectively, for chest CT, and 5–14 mGy and 3–9 mSv, respectively, for abdominopelvic CT. Doses to organs at the boundaries of the scan length were higher for 64-slice CT scanners using large beam widths and/or a large pitch because of the larger extent of over-ranging. The CT dose index (CTDI(vol)), dose–length product (DLP) and the effective dose values using 64-slice CT for the adult and paediatric phantoms were the same as those obtained using 4-, 8- and 16-slice CT. Conversion factors of DLP to the effective dose by International Commission on Radiological Protection 103 were 0.024 mSv⋅mGy(−1)⋅cm(−1) and 0.019 mSv⋅mGy(−1)⋅cm(−1) for adult chest and abdominopelvic CT scans, respectively.